Camera motion estimation and object extraction using multiple consecutive frames with ghost and noise removal for pan-tilt-zoom-camera - Syaimaa' Solehah Mohd Radzi (School of Computer and Communication Engineering, University Malaysia Perlis, 2014)
This research presents a new algorithm for extracting moving objects using Pan-Tilt-Zoom (PTZ) camera. Previously, system that uses moving camera faces some problems, including misalignment between current and template frames, appearance of unwanted objects (ghost), illumination changes, shadow and crowd. This research developed an algorithm to avoid misalignment images, remove ghost and noises.